Dynamics of West Nile virus evolution during infection of wild birds, mosquitoes, and the human brain: unraveling the complexities of selection, drift, and fitness - Grubaugh, Nathan D., author; Ebel, Gregory D., advisor; Black, William C., committee member; Foy, Brian D., committee member; Brault, Aaron C., committee member; Sloan, Daniel B., committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.